Avaliação de diferentes substratos na produção de mudas e Sebastiania Commersoniana (Baillon) L. B. Smith e R. J. Downs - Mula, Horácia Celina Armando (2011)
Orientador : Prof. Dr. Antonio Carlos Nogueira